Community environmental education and the roles of international aid agencies : a case study of Mai Ja Yang Community, Kachin State, Myanmar - Nang Thinn Thinn Tun (Chulalongkorn University, 2013)
Thesis (M.A.)--Chulalongkorn University, 2008